2017
DOI: 10.1073/pnas.1707937114
|View full text |Cite
|
Sign up to set email alerts
|

EIN2 mediates direct regulation of histone acetylation in the ethylene response

Abstract: Ethylene gas is essential for developmental processes and stress responses in plants. Although the membrane-bound protein EIN2 is critical for ethylene signaling, the mechanism by which the ethylene signal is transduced remains largely unknown. Here we show the levels of H3K14Ac and H3K23Ac are correlated with the levels of EIN2 protein and demonstrate EIN2 C terminus (EIN2-C) is sufficient to rescue the levels of H3K14/23Ac of ein2-5 at the target loci, using CRISPR/dCas9-EIN2-C. Chromatin immunoprecipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 56 publications
1
89
0
Order By: Relevance
“…Full- 25 length CTR1 also interacted with the EBFs in a BiFC assay ( Fig.5e). EIN2-CEND reconstituted YFP signals with its known nuclear interacting protein, EIN2 NUCLEAR-ASSOCIATED PROTEIN 1 (ENAP I) in the nucleus ( Supplementary Fig.5) 29 , showing that EIN2-CEND was present in the nucleus. Full-length CTR1 interacted with EBF1 and 2 regardless of ACC treatment ( Fig.5e and Supplementary Fig.6), which was consistent with constitutive nuclear localization of CTR1 in CaMV 35S overexpression lines ( Fig.1h).…”
Section: Ctr1 Promotes Degradation Of Ein3 Via Ebfs Without Kinase Acmentioning
confidence: 93%
“…Full- 25 length CTR1 also interacted with the EBFs in a BiFC assay ( Fig.5e). EIN2-CEND reconstituted YFP signals with its known nuclear interacting protein, EIN2 NUCLEAR-ASSOCIATED PROTEIN 1 (ENAP I) in the nucleus ( Supplementary Fig.5) 29 , showing that EIN2-CEND was present in the nucleus. Full-length CTR1 interacted with EBF1 and 2 regardless of ACC treatment ( Fig.5e and Supplementary Fig.6), which was consistent with constitutive nuclear localization of CTR1 in CaMV 35S overexpression lines ( Fig.1h).…”
Section: Ctr1 Promotes Degradation Of Ein3 Via Ebfs Without Kinase Acmentioning
confidence: 93%
“…Second, it has been fused with green fluorescent protein for the dynamic imaging of genomic loci . Third, the fusion of dCas9 to histone modifiers (e.g., methylase, demethylase, or acetyltransferase) or other proteins involved in DNA methylation has been used for targeted epigenetic regulation …”
Section: Crispr/cas9‐created Mutations In Plantsmentioning
confidence: 99%
“…It has been recently shown that VFP3/ENAP1 is involved in ethylene response. VFP3/ENAP1 interacts with EIN2, EIN3, SRT1 and SRT2 and regulates change in histone H3 acetylation levels and ethylene-dependant transcription [28][29][30]. Using a GFP transcriptional fusion protein, we investigated the subcellular localization of OBE1 and VFP3/ENAP1.…”
Section: Rbl Interacts With Obe1 and Vfp3/enap1mentioning
confidence: 99%